The democratic nature and the social construction of historical truth and its relationship with the state, the military regime and civil society: introductory aspects - Gesta Leal, Rogério (Universidad Nacional del Litoral, 2014)
This essay is a preliminary approach of the democratic nature of the historical truth and its social construction, considering the deliberative democratic paradigm of inclusion of citizens in the process of examination and clarification of the acts of disappearances, abductions, killings and torture committed during the period of the Brazilian military regime from 1964 to 1985 and aims to broadly analyze the conditions and possibilities of social participation in the Truth Commission in Brazil. For this purpose, at first will be shown the journeys and challenges from the representative democracy to the participatory and deliberative democracy, in a second moment it will be analyzed the importance of historical truth under the power schemes, as well as memory as a fundamental right to a new democracy and finally, it will me examined the conditions and possibilities of social participation in the Truth Commission in Brazil.